2015
DOI: 10.1371/journal.ppat.1004594
|View full text |Cite
|
Sign up to set email alerts
|

A Human Type 5 Adenovirus-Based Trypanosoma cruzi Therapeutic Vaccine Re-programs Immune Response and Reverses Chronic Cardiomyopathy

Abstract: Chagas disease (CD), caused by the protozoan Trypanosoma cruzi, is a prototypical neglected tropical disease. Specific immunity promotes acute phase survival. Nevertheless, one-third of CD patients develop chronic chagasic cardiomyopathy (CCC) associated with parasite persistence and immunological unbalance. Currently, the therapeutic management of patients only mitigates CCC symptoms. Therefore, a vaccine arises as an alternative to stimulate protective immunity and thereby prevent, delay progression and even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 52 publications
6
92
0
Order By: Relevance
“…Ultimately, Tc24 may be combined with other T. cruzi antigens, such as TSA1, TcG2, and TcG4 to increase vaccine efficacy. 22,24,29,30,58 Additionally, this vaccine could potentially be tested in combination with reduced dose chemotherapy. 15 If the vaccine provides a dose-sparing effect on the chemotherapeutic agents, the side effect profile could be minimized while increasing efficacy though multiple parasite killing mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, Tc24 may be combined with other T. cruzi antigens, such as TSA1, TcG2, and TcG4 to increase vaccine efficacy. 22,24,29,30,58 Additionally, this vaccine could potentially be tested in combination with reduced dose chemotherapy. 15 If the vaccine provides a dose-sparing effect on the chemotherapeutic agents, the side effect profile could be minimized while increasing efficacy though multiple parasite killing mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…23,27 In particular, production of IFNg is critical for control of T. cruzi infection, unlike IL-4, a T H 2-associated cytokine. 23,[28][29][30] Nanoparticles have been shown to increase antigen uptake by antigen-presenting cells 31 and enhance the T H 1-mediated CD8 C T cell response [32][33][34] through increased MHC I antigen presentation. 35 Nanoparticles can also serve as a depot for antigen, 36 allowing prolonged stimulation of the T H 1 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Altering these progressive changes in CD8 + T cell function could improve the prognosis of chronic chagasic myocarditis. Indeed, the results of studies using mouse models have suggested that the application of genetic vaccination with recombinant adenoviruses can reprogram this deleterious immune response and attenuate chronic chagasic myocarditis (98).…”
Section: Cd8mentioning
confidence: 99%
“…3 and 6). Recently, Pereira et al 44 have highlighted the importance of reprogramming the immune response to preserve and recover tissue injury in Chagas heart disease induced by parasite infection.…”
Section: Discussionmentioning
confidence: 99%